Pengaruh Kemiskinan dan Kesempatan Kerja Terhadap Indeks Pembangunan Manusia di Provinsi Sulawesi Tenggara - M., Mutmainnah; Harafah, La Ode Muh.; Saranani, Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of poverty and employment opportunities on the human development index (HDI) in Southeast Sulawesi Province. This study uses a quantitative approach with an explanatory research method. The data used in this study are poverty data (X1) and employment opportunities (X2) and the human development index (Y) in 17 regencies/cities in Southeast Sulawesi Province with an observation period of 5 years (2019-2023). The data analysis technique in this study is Panel Data Regression Analysis using Eviews 12. The results of the study show that poverty has a negative and insignificant effect on the Human Development Index (HDI) in Southeast Sulawesi Province. This shows that if poverty increases, the Human Development Index will decrease and employment opportunities have a positive and significant effect on the Human Development Index (HDI) variable in Southeast Sulawesi Province. This shows that if employment opportunities increase, the Human Development Index will also increase.